Prevalence and antifungal susceptibility of Candida albicans and its related species (C. dubliniensis and C. africana) isolated from vulvovaginal samples in a teaching hospital of Argentina - Raspanti, Claudia Gabriela (2016)
Coagulase-negative staphylococci (CNS) are a common cause of bovine subclinicalmastitis (SCM). The prevalence of CNS species causing SCM identified by genotyping varies among countries. Overall, the antimicrobial resistance in this group of organisms is increasing worldwide; however, little information exists about a CNS species resistant to antibiotics. The aim of the present study was to genotypically characterize CNS at species level and to determinethe prevalence and antibiotic resistance profiles of CNS species isolated from bovine SCM in 51 dairy herds located in the central region of the province of Cordoba, Argentina. In this study, we identified 219 CNS isolates at species level by PCR-restriction fragment length polymorphism of the groEL gene. Staphylococcus chromogenes (46.6%) and Staphylococcus haemolyticus (32%) were the most prevalent species. A minimum of three different CNS species were present in 41.2% of the herds. S. chromogenes was isolated from most of the herds (86.3%), whereas S. haemolyticus was isolated from 66.7% of them. The broth microdilution method was used to test in vitro antimicrobial susceptibility. Resistance to a single compound or two related compounds was expressed in 43.8% of the isolates. S. chromogenes and S. haemolyticus showeda very high proportion of isolates resistant to penicillin. Resistance to two or more non-related antimicrobials was found in 30.6% of all CNS. S. haemolyticus exhibited a higher frequency of resistance to two or more non-related antimicrobials than S. chromogenes